Recurrent Episodes of Diffuse Alveolar Hemorrhage in Systemic Sclerosis 30 Days Apart - Hussien Saab MD; Tushar Bajaj MD; Kirandeep Bains BS; Ralph Garcia-Pacheco MD (SAGE Publishing, 2019)
Diffuse alveolar hemorrhage (DAH) is a life-threatening clinicopathologic condition caused by accumulation of intra-alveolar red blood cells (RBCs) after disruption of the alveolar-capillary basement membrane that is often seen as a complication of various diseases, but is rare in systemic sclerosis. A 46-year-old female with systemic sclerosis presented to the emergency department complaining of right-sided chest pain. Initially, her electrocardiogram and chest X-ray (CXR) were unremarkable; however, she progressively decompensated into acute respiratory failure resulting in intubation. Repeat CXR and computed tomography scan showed diffuse bilateral alveolar infiltrates and pleural effusions. Video bronchoscopy with bronchoalveolar lavage showed numerous RBCs, neutrophils, macrophages, and respiratory epithelial cells consistent with acute DAH. She was started on intravenous pulse-dosing Solu-Medrol 1 g daily for 5 days. One month later, the patient returned with intractable nausea and vomiting. Again, she went into acute respiratory distress with a PaO 2 of 59 while on a 10-L non-rebreather mask. CXR revealed development of alveolar infiltrates in the right lung. A bronchoscopy with bronchoalveolar lavage again showed numerous RBCs and neutrophils along with staining positive for hemosiderin-laden macrophages. Systemic sclerosis with alveolar hemorrhage is a rare occurrence; however, most cases are single episodes of hemorrhage, whereas we present a case with 2 confirmed episodes within 30 days. Its life-threatening nature makes a systemic approach and aggressive treatment crucial to decreasing morbidity and mortality-making it a diagnosis that should not be overlooked, especially in patients with nonspecific symptoms.